From Population Lending to HNP Results : The Evolution of the World Bank's Strategies in Health, Nutrition and Population - Fair, Mollie (Washington, DC : World Bank, 2012)
This paper reviews the evolution of the World Bank's strategies in the health, nutrition, and population (HNP) sector in relation to both internal and global events, as background for the forthcoming evaluation by the Independent Evaluation Group (IEG) of the Bank's support for HNP. It summarizes the objectives, priorities, and strategies in HNP as expressed in official documents and revealed implicitly by its lending and non-lending activities. Special emphasis is placed on analysis of the period since the release of the 1997 HNP Strategy, which has guided the sector over the last decade. However, the report also reviews the Bank's earlier experiences in HNP, so as to provide a context for understanding the World Bank's current strategies. Detailed timelines annexed to the paper help to put the Bank's strategies and actions in the context of the evolution of global HNP themes. It aimed to help client countries: (i) improve the HNP outcomes of the poor and protect the population from the impoverishing effects of illness, malnutrition, and high fertility; (ii) enhance the performance of health systems; and (iii) secure sustainable health financing. The sector sought to achieve greater impact through emphasizing strategic policy directions in country assistance strategies, underpinning lending with analysis and research, increasing selectivity, improving client services, and stronger monitoring and evaluation. Throughout the recent phases, the World Bank's objectives remained largely consistent: improving health outcomes, especially among the poor; strengthening health systems; and securing sustainable financing. This review of the Bank's objectives and strategies, particularly over the past decade, suggests four priority areas of investigation for an evaluation of the Bank's HNP support.